Nutrition : Vol. 1 - Richman, Sharon; Ortiz, Dawn (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. ; Amenia, NY : Grey House Publishing, Inc., 2016)
"Salem Health's newest title, Nutrition, offers researchers a one-stop source for comprehensive, easy-to-understand information on all aspects of human nutrition. This new tool is designed to inform users about healthy eating, the nutritional value of various foods, diets, eating disorders, dietary conditions and so much more. Salem Health: Nutrition provides in-depth articles on 300 topics in an easy-to-use A-Z format. Designed for high school, undergraduate and public libraries, entries are written in clear, understandable language to provide students and researchers with accessible, updated information important to gain an understanding of the many areas of human nutrition. Written by healthcare experts, the entries in Salem Health: Nutrition offer a comprehensive overview of a wide variety of topics, including: Dietary Condition; Diets; Ethnic & Cultural References; Healthy Eating; Nutritional Health for Various Age Groups; Skills & Checklists; Vitamins & Minerals; Dietary Guidelines; Eating Disorders; Foods; Nutrition Best Practices; Obesity; and Supplements"--
Volume 1. Food Groups ; Fruits ; Vegetables ; Grains ; Proteins ; Dairy ; Beverages ; Herbs & Spices ; Fats & Oils --
Includes bibliographical references and index.
106840
Keywords: Nutrition -- Encyclopedias; Encyclopedias